Comparative assessment of the tendency to biodegradation of traditional and alternative aviation fuels - Matvieieva, Olena; Vovk, Yuliia (Problems of Environmental Biotechnology, 2021)
The study of fuel resistance to microbiological damage was determined experimentally by visual inspection of samples, as well as such indicators as corrosion and acidity.